New species of Achirus (Pleuronectiformes: Achiridae) from Northeastern Brazil - Ramos, Robson T. C.; Ramos, Telton P. A.; Lopes, Paulo R. D. (Zootaxa, 2009)
Eight species are considered valid in the genus Achirus (Lacépède), distributed on both sides of the Americas, mainly in marine and estuarine waters with A. novoae being the only species of this genus restricted to freshwaters of the Orinoco basin and its delta. A new species, A. mucuri, is described from the estuary of the Mucuri River, a small system in Bahia state, northeastern Brazil. A. mucuri differs from congeners, except A. novoae, in having a connection between the branchiostegal membrane and the isthmus. A. mucuri differs from A. novoae in its labial fimbriae and latero-sensory cephalic canal pattern.